Under the oak tree : the comic. 1 - Kim, Suji; Namu (Author) (Inklore, 2024)
"Most fairytales end with a wedding and a happily-ever-after -- but this is no fairytale. When stuttering Lady Maximilian is forced to marry Sir Riftan, a lowborn knight caught in one of her father's schemes, her stumbling communication and his gruff manner sour their relationship before it can begin. Riftan leaves for war the morning after their disastrous wedding night, and it's three years until Maxi sees him again. Now the husband she barely knows is a war hero. And when he comes home to claim her, Maxi will need to master her own bewildering desire -- and Riftan's -- before she can hope to become the true mistress of their enormous castle estate. That task will demand courage from Maxi, even as she struggles to find her own voice." --